INTEGRALISM AS A NECESSARY DIRECTION IN SOCIO-ECONOMIC RESEARCH OF MODERN SOCIETY - Aleksandrova, Elena V.; Kovnir, Vladimir N.; Skripnikova, Marina I.; Lisovskaya, Ekaterina G.; Rozhanskaia, Elena A. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Annotation. The article is devoted to the consideration of some early works of P. Sorokin. Relevance of the topic. A brief study of the sociology of integralism is proposed. Integralism is the viewpoint that defines society as a whole. Pitirim Sorokin develops his study of integralism in the work "Social and Cultural Dynamics". Sorokin believed that it was necessary to study society in a comprehensive way, in other words, perceiving a person in its integral essence. Laws operating in nature are aimed at achieving stability, interaction and cooperation. Social phenomenon should bring balance to the society and the main task of sociology is to determine in what ratio they all are situated. The main methods of research are methods of comparative analysis, theoretical and methodological approaches. The aim of the work is to study the role of integral sociology and its impact on modernity. The novelty of research lies in the modern approach to the integral concepts developed by P.Sorokin.